Time, Migration and Forced Immobility : Sub-Saharan African Migrants in Morocco - Stock, Inka (Book collections on Project MUSE., 2019)
This book is concerned with the effects of migration policy making in Europe on migrants in the Global South and links insights on immobility to social theories of time to examine the human consequences of current migration dynamics from the perspectives of migrants themselves. Based on in-depth ethnographic research, this is an invaluable learning resource that aims to challenge current international migration politics and policy-making.